2017
DOI: 10.1371/journal.pone.0185879
|View full text |Cite
|
Sign up to set email alerts
|

Change in inflammatory parameters in prefrail and frail persons obtaining physical training and nutritional support provided by lay volunteers: A randomized controlled trial

Abstract: The aim of the study was to compare the effects of home visits with physical training and nutritional support on inflammatory parameters to home visits with social support alone within a randomized controlled trial. Prefrail and frail persons received home visits from lay volunteers twice a week for 12 weeks. Participants in the physical training and nutritional intervention group (PTN, n = 35) conducted two sets of six strength exercises and received nutritional support. The social support group (SoSu, n = 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 64 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…However, several studies have shown the beneficial effects of physical training in RA patients [ 29 , 37 ], and physical training should, therefore, be implemented in RA patients for many different reasons. In addition, the effect of physical training on chronic inflammation has been shown in several studies [ 38 , 39 ], and this could, in addition to many other benefits, also improve sexual function. Furthermore, our results, in line with other studies, show how frequent sexual problems are in patients with RA, and it is, therefore, necessary to address sexual health and actively ascertain sexual function in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown the beneficial effects of physical training in RA patients [ 29 , 37 ], and physical training should, therefore, be implemented in RA patients for many different reasons. In addition, the effect of physical training on chronic inflammation has been shown in several studies [ 38 , 39 ], and this could, in addition to many other benefits, also improve sexual function. Furthermore, our results, in line with other studies, show how frequent sexual problems are in patients with RA, and it is, therefore, necessary to address sexual health and actively ascertain sexual function in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the previously mentioned lack of a standard definition for frailty, only studies utilizing a valid construct to define frailty for inclusion criteria were included. In total, 8 studies were included in this narrative review [15][16][17][18][19][20][21][22] (results from one intervention was published in four separate articles) [15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed 8 studies (Table 1) [15][16][17][18][19][20][21][22]. The analyzed interventions included a total sample of 1030 communityliving older adults (53% women) with a mean age of 79.6 ± 7.1 years.…”
Section: Participants and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations